Method Development and Syntheses Examples of Isotopically Labeled Compounds to Foster Operational Excellence in Pharma Industry - Sib, Anna; Derdau, Volker (Synlett, 2024)
The different topics and synthetic approaches in an isotope chemistry laboratory of a pharma company are described. Besides the challenges in the synthesis of long-lived isotopes such as 3H or 14C, short-lived isotopes such as 68Ga and stable isotopes such as 15N, 13C or 2H approaches for the isotopic labeling are also demonstrated. Furthermore, method development with emphasis on collaborations with academic groups to tackle the future challenges are discussed.1 Introduction2 Isotopic Labeling with Hydrogen Isotopes Deuterium (2H, D) and Tritium (3H, T)2.1 Deuterium Labeling for MS Standards2.1.1 Labeled Nitrosamines – The Hunt to Quantify Hazardous Impurities2.1.2 Deuterated Drugs, an Approach To Improve Existing Drugs or To Find Opportunities in Drug Discovery2.2 Tritium-Labeling Methods – The Fast Approach to Radioactively Labeled Compounds2.2.1 Hydrogen Isotope Exchange by Iridium Catalysis2.2.2 Ruthenium-Catalyzed HIE2.2.3 Nanoparticles as Catalysts in HIE2.2.4 Photoredox-Catalyzed HIE2.2.5 HIE via Classical Radical Mechanism2.2.6 Beyond HIE – Halogen–Tritium Exchange3 Challenges in 14C-Synthesis Projects4 Short-Lived Isotopes – The Need for Speed5 Beyond Isotope Science – Late-Stage Functionalization5.1 Examples of Late-Stage Functionalization for Peptides5.2 Examples of Catalyst-Controlled Late-Stage Functionalization6 Conclusion
Keywords: isotope science; drug discovery; isotope exchange; CH functionalization; catalysis